"Layer‐Filter Threshold" Technique for Near‐Infrared Laser Ablation in Organic Semiconductor Device Processing. (10th June 2015) - Ye, Feng; Chen, Zhaobin; Zhao, Xiaoli; Chen, Jiayue; Yang, Xiaoniu
Abstract : Although conventional laser ablation (CLA) method has widely been used in patterning of organic semiconductor thin films, its quality control still remains unsatisfied due to the ambiguous photochemical and photothermal processes. Based on industrial available near‐infrared laser source, herein, a novel "layer‐filter threshold" (LFT) technique is proposed, which involves the decomposition of targeted "layer‐filter" and subsequent explosive evaporation process to purge away the upper layers instead of layer‐by‐layer ablation. For photovoltaic device with structure of metal/blend/PEDOT:PSS/ITO/glass, the PEDOT:PSS layer as the "layer‐filter" is first demonstrated to be effective, and then the merged P1–P2 line and metal electrode layer are readily patterned through the "self‐aligned" effect and regulation of ablation direction, respectively. The correlation between laser fluence and explosive ablation efficacy is also investigated. Finally, photovoltaic modules based on classical P3HT:PC61 BM and low‐bandgap PBDT‐TFQ:PC71 BM systems are separately fabricated following the LFT technique. It is found that over 90% of geometric fill factor is achieved while device performances maintain in a limited change with increased number of series cells. In comparison to conventional laser ablation methods, the LFT technique does not require sophisticated instruments but reaches comparable processing accuracy, which shows promising potential in the fabrication and commercialization of organic semiconductor thin‐film devices. Abstract : Layer‐filter threshold (LFT) technique based on near‐infrared laser is proposed and demonstrated, which enables the patterning strategy through an interlayer explosion effect with high precision and easily reachable operating conditions. Thus obtained organic photovoltaic modules reach geometric fill factors exceeding 90% and maintain the performances with increasing number of interconnected cells, which verifies the potential of LFT technique in the patterning of organic semiconductor devices.